Patient safety culture in hospital maternity care: an integrative review of midwives and nurses - Nor Amal Hazirah Hassan; Damia Hazimah Asnawi; Amal Amirah Asri; Hanif Abdul Rahman; Khadizah H Abdul-Mumin (British Journal of Midwifery, 2026)
Background/Aims Safety is a central element of maternity care. Despite global efforts to reduce maternal harm, preventable adverse events can still take place at hospital maternity services. This integrative review consolidates research on midwives' and maternity nurses' perceptions of patient safety culture, identifying key practices, barriers and facilitators in hospital maternity care. Methods PubMed, Scopus, ProQuest and Google Scholar were searched for studies published between 2014 and 2024 that explored healthcare professionals' experiences with patient safety culture at maternity units. The included studies' findings were analysed and structured according to the seven common patient safety culture dimensions. Results Nine studies were included. Common assessment tools were the Hospital Survey on Patient Safety Culture, Safety Attitudes Questionnaire and Safety Climate Scale. Teamwork in units was commonly reported as positive. Key challenges included hierarchical barriers, inadequate managerial support, staff shortages and workload pressures. Conclusions Midwives perceive teamwork as a strength in patient safety culture, but report systemic gaps in error reporting and leadership support. Implications for practice Addressing the identified gaps through non-punitive policies, interdisciplinary collaboration and resource allocation could improve safety in maternity care.